#### Answer

$2$

#### Work Step by Step

$x^{-6}=\dfrac {1}{64}=\dfrac {1}{2^{6}}\Rightarrow x^{-6}=2^{-6}\Rightarrow x=2$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$2$

$x^{-6}=\dfrac {1}{64}=\dfrac {1}{2^{6}}\Rightarrow x^{-6}=2^{-6}\Rightarrow x=2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.